A 23bp Insertion in the Endothelial Protein C Receptor (EPCR) Gene Impairs EPCR Function - Biguzzi, Eugenia; Merati, Giuliana; Liaw, Patricia C. Y.; Bucciarelli, Paolo; Oganesyan, Natalia; Qu, Dongfeng; Gu, Jian-Ming; Fetiveau, Raffaela; Esmon, Charles T.; Mannucci, Pier Mannuccio; Faioni, Elena M. (Thrombosis and Haemostasis, 2001)
EPCR is a type I transmembrane protein, highly expressed on the endothelium of large vessels, that binds protein C and augments its activation. In this study, a 23bp insertion in the EPCR gene was found in 4/198 survivors of myocardial infarction and 3/194 patients with deep vein thrombosis. The EPCR gene with the insertion predicts a protein that lacks part of the extracellular domain, the transmembrane domain and the cytoplasmic tail. Expression studies showed that the truncated protein is not localized on the cell surface, cannot be secreted in the culture medium, and does not bind activated protein C. Since protein C activation depends on the concentration of EPCR, patients with the EPCR insertion could have a diminished protein C activation capacity. Further clinical studies of adequate samples size are necessary to establish whether or not the EPCR insertion predisposes to the development of thrombotic events.
Keywords: Endothelial protein C receptor; myocardial infarction; deep veinthrombosis; gene mutations